Potensi Cendawan Entomopatogen Verticillium lecanii dan Beauveria bassiana dalam Mengendalikan Wereng Hijau dan Menekan Intensitas Penyakit Tungro - Ladja, Fausiah T.; Santoso, Teguh; Nurhayati, Endang (Jurnal Penelitian Pertanian Tanaman Pangan, 2011)
Pests and diseases cause significant rice yield losses every planting season. One of the important rice disease is tungro, a virus disease transmitted by green leafhoppers (Nephotettix virescens Distant), that can cause yield losses of up to 90%. This study was aimed to determine the effectiveness of entomopathogenic fungi Verticillium lecanii and Beauveria bassiana to control N. virescens as a vector of the tungro virus. The experiment was arranged in a randomized complete block design with two factors. The first factor was conidial density of the fungi and the second factor was period of food acquisition. The variables observed were mortality and the ability to fly of N. virescens at 3, 7, 10, and 14 days after application (DAA), tungro disease symptoms, virus incubation periods, disease incidences, plant heights, and number of tillers. The results showed that applications of B. bassiana (107 conidia/ml) and V. lecanii (108 conidia/ml) caused death of green leafhoppers within 3-14 DAA. Based on the virus incubation period and the incidence of the tungro disease, application of the entomopathogenic fungi did not affect the ability of N. virescens to transmit tungro virus.